What is the contribution of John Dewey about the teacher's role in moral education? - Josu Ahedo Ruiz (FahrenHouse, 2018)
In Dewey's educational conception the student is protagonist because learning requires as a condition the student's interest. Nevertheless, the teacher's role is not secondary because it consists in helping student to discover which his interests are and teaching him the method that is necessary to think about social reality. The Hegelian influence is observed in Dewey by his attempt of overcoming the dualisms epistemological, ontological and morally. The end of the society is the same that of the education and of every individual and consists in social improvement. Dewey does not accept that end is something external to the action, thus he identifies ends with means. This is only possible through of a method founded on the experience and that it culminates in the experience because the social improvement needs that the own social reality is the starting point. This method bases his pragmatism turning into action in instrumental as the way necessary for social reform. The teacher is responsible for moral education and he must achieve student thinks about social reality, looking for its improvement, and this makes meaning to character education.